Study of the Prophet's Prediction Hadith - Yahya, Agusni (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
This study aims to describe the interpretation of prophetic hadiths concerning the predictions by the Prophet as a guide for the future and how the methodology of understanding hadith contributes to a correct interpretation of these statements. This study uses a qualitative approach with a literature review method. This study showed that the predictions made by Prophet Muhammad in hadiths about the state of the community are not necessarily meant to be seen as inevitable destinies but rather as events that will unfold. The negative interpretations of these predictions have led to a loss of relevance in the present era. However, by understanding the distinctive characteristics of hadiths and applying the knowledge of fiqh al-hadith, one can better comprehend the statements of Prophet Muhammad SAW.